Indium-mediated regioselective synthesis of ketones from arylstannanes under solvent-free ultrasound irradiation - Lo Fiego, Marcos Jacinto (2013)
The solvent-free indium-promoted reaction of alkanoyl chlorides with sterically and electronically diverse arylstannanes is a simple and direct method for the regioselective synthesis of primary, secondary and tertiary alkyl aryl ketones in good to excellent isolated yields (42–84%) under mild and neutral conditions. The protocol is also adequate for the synthesis of aryl vinyl ketones. Reaction times are drastically reduced (from 3–32 h to 10–70 min) under ultrasonic irradiation. Evidences for the involvement of a homolytic aromatic ipso-substitution mechanism, in which indium metal acts as radical initiator, are presented. It is possible the transference of two aryl groups from tin, thus improving effective mass yield, working with diarylstannanes as starting substrates.